BIOPHYSICAL THERAPY USING FREQUENCY-EMITTING DEVICES: CURRENT PERSPECTIVES IN HUMAN HEALTH - de Assis Limeira Junior, Francisco (Health and Society, 2025)
Frequency-based therapy, which employs devices that emit electromagnetic signals or microcurrents with predefined parameters, is increasingly recognized within integrative and complementary health practices. Modalities such as pulsed electromagnetic fields (PEMF), frequency-specific microcurrent (FSM), and bioresonance demonstrate growing evidence of bioelectric and bioenergetic modulation with therapeutic relevance. Proposed mechanisms include effects on ion channels, calcium flux, mitochondrial ATP synthesis, epigenetic modulation, and reorganization of vibrational patterns associated with biophoton-mediated cellular communication. From the perspective of vibrational medicine and quantum biophysics, these technologies act on the coherence of the human energetic field, supporting systemic balance.The reviewed literature indicates consistent, although protocol-dependent, benefits in musculoskeletal pain, osteoarthritis, bone and soft tissue healing, and reductions in depressive symptoms. Clinical trials and case series report functional improvements, analgesia, and accelerated tissue repair. Clinical experience with ILIB, Laser therapy, and frequency-emitting devices such as the PC Zapper II supports these findings, showing positive outcomes also in cardiovascular dysfunctions, infectious processes, metabolic imbalance, and emotional conditions. The safety profile is favorable, with a low incidence of adverse effects when contraindications, such as pacemakers, pregnancy, and uncontrolled epilepsy are observed. Despite promising results, methodological limitations remain, including small sample sizes, heterogeneity of parameters, and lack of device standardization. These constraints highlight the need for more rigorous, multicenter randomized trials. Frequency therapy should be understood as a complementary intervention, not a substitute for conventional treatment, offering enhanced clinical outcomes, reduced medication burden, and improved quality of life. The growing evidence base justifies further investigation to consolidate its scientific foundations and clinical applicability.